1996
DOI: 10.1074/jbc.271.47.29839
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Mediating Parathyroid Hormone Stimulation of Bone Sialoprotein Gene Expression in Osteoblasts

Abstract: Bone sialoprotein is a major noncollagenous protein of bone. Parathyroid hormone (PTH) was shown to cause a 2-4-fold increase in the steady-state levels of bone sialoprotein mRNAs within primary cultures of embryonic osteoblasts. The induction could be mimicked by both forskolin and phorbol 12-myristate 13-acetate and was not inhibited by cycloheximide. Transient expression of a ϳ1200-base pair avian 5 bsp promoter/reporter construct demonstrated similar inductions as mRNA levels. Co-transfection of an express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 50 publications
1
25
2
Order By: Relevance
“…Boguslawski et al (30) observed that rat and human osteoblast-like cell lines stably transfected with osteocalcin promoter reporter construct responded to parathyroid hormone and growth factors ( fibroblast growth factor-2 and insulin-like growth factor-I) via enhanced osteocalcin transcription mediated by a PKA-dependent pathway. A similar activation of bone sialoprotein promoter activity was documented for fibroblast growth factor-2 (54, 56), parathyroid hormone (33,53), and prostaglandin E 2 (34) in which bone sialoprotein transcription was stimulated through a PKA-dependent pathway, although a protein kinase C-mediated pathway may play a minor role (33). The present study differs from previous reports in two important aspects.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Boguslawski et al (30) observed that rat and human osteoblast-like cell lines stably transfected with osteocalcin promoter reporter construct responded to parathyroid hormone and growth factors ( fibroblast growth factor-2 and insulin-like growth factor-I) via enhanced osteocalcin transcription mediated by a PKA-dependent pathway. A similar activation of bone sialoprotein promoter activity was documented for fibroblast growth factor-2 (54, 56), parathyroid hormone (33,53), and prostaglandin E 2 (34) in which bone sialoprotein transcription was stimulated through a PKA-dependent pathway, although a protein kinase C-mediated pathway may play a minor role (33). The present study differs from previous reports in two important aspects.…”
Section: Discussioncontrasting
confidence: 55%
“…The cAMP-responsive element (CRE), a cis-element, interacts with a basic domain/leucine zipper motif contained within a transcription factor termed CRE-binding protein (CREB) through the cAMP-dependent PKA pathway (32). Studies in which both osteocalcin (30) and bone sialoprotein (33,34) promoter activities were stimulated by the cAMPdependent PKA pathway suggest the presence of the putative CRE site within these promoter regions that may interact with CREB to initiate osteocalcin and bone sialoprotein expression.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, PTH inhibits bone marker gene expression and mineralization in differentiated osteoblasts and cementoblasts (49,56). In contrast, PTH rapidly induces osteoblastspecific gene expression in undifferentiated, proliferating osteoblasts (8,16,57,58). Thus, PTH may preferentially stimulate osteoblast differentiation in immature cells while inhibiting it in more mature cells.…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%
“…The plasmid construct containing bp Ϫ1,239 to ϩ25 of the BSP promoter in the sense direction relative to the CAT coding sequence in the pCAT basic vector (Promega Corp.) was previously described (59). Nested deletions from the 5Ј end of the BSP promoter were generated by PCR amplification of selected segments of the promoter from bp Ϫ620, Ϫ524, or Ϫ131 to ϩ25 and have been previously described (58). Site-directed mutagenesis was performed to incorporate 2-nucleotide substitutions into the core binding motif (TGG) of each individual Cbfa site (Fig.…”
Section: Methodsmentioning
confidence: 99%